Floating Multiparticulate Drug Delivery Systems: An Overview - Y. S. GATTANI (International Journal of Pharma and Bio Sciences, 2010)
In recent scientific and technological advancement have been made in the research and development of rate controlled oral drug delivery systems overcoming physiological adversities, such as short gastric residence times (GRT) and unpredictable gastric emptying times (GET). Furthermore, absorption windows in the proximal gut can limit the bioavailability of orally administered compounds and can be a major obstacle to the development of controlled release formulations for important drugs. Methods to increase the residence of drug formulations at or above the absorption window are discussed in this review1. Several approaches are currently utilized in the prolongation of the GRT, including floating drug delivery system (FDDS), also known as hydro dynamically balanced systems (HBS), swelling and expanding systems, modified shape systems and high density system. In this review, the current status of floating multiparticulate drug delivery systems including hollow microspheres (micro balloons), low density floating micro pellets and floating micro beads (acrylic resin based), microcapsules etc, their evaluation parameter, advantages, application, limitation and future potential for oral control drug delivery are discussed.